UPLC-MS/MS Analysis of Hydroxyanthracene Derivatives in Botanical Food Products and Supplements: Surveillance of the Italian Market - Mariantonietta Peloso; Alessandro Capriotti; Damiano Accurso; Elena Butovskaya; Giorgio Fedrizzi; Elisabetta Caprai (Foods)
Hydroxyanthracene derivatives (HADs) are natural compounds that occur in several botanical species belonging to the genera Aloe L., Cassia L., Rheum L., Frangula Mill., and Rhamnus L. While they are widely used for their laxative effects, concerns persist about their potential genotoxicity and carcinogenicity. This study presents the development, validation, and application of a sensitive and rapid LC-MS/MS method to detect HAD (aloins, aloe-emodin, emodin, and danthron) levels in botanical food products and supplements. The method was validated according to criteria established by the European Union Reference Laboratory for Mycotoxins and Plant Toxins, and Regulation (EU) No 2783/2023 and was demonstrated to be fit-for-purpose. It was applied to 43 samples collected from the Italian market, including beverages, liquid and solid food supplements, herbal infusions, and jam based on aloe, senna, cassia, rhubarb, and frangula. The results revealed that 33% of the analyzed samples contained detectable HAD concentrations above the limit of quantification (LOQ = 0.5 mg/kg). The highest concentrations, up to 1352.9 mg/kg for the sum of aloin A and B, were found in solid food supplements derived from senna, cascara, rhubarb, and frangula. Aloe-emodin reached 213.4 mg/kg in a solid food supplement sample containing the same plant species, while the maximum detected concentration of emodin was 259.7 mg/kg in a senna-based supplement. No sample contained danthron. Conversely, in the majority of aloe beverage samples, HAD levels were found to be below the LOQ. In order to ensure the safety of consumers, it is essential that a more rigorous market surveillance of botanical food products is implemented, along with further toxicological studies.